Uso da escarificação na adolescência: uma análise winnicottiana de um caso clínico - Rezende, Natália Barros de (2021)
The purpose of the dissertation is to reflect on the act of scarification, or self-mutilation in adolescence, through the psychoanalytical conceptual and more specifically within the Winnicottian Theory, from the psychotherapeutic care of a clinical case of an adolescent. It seeks to understand how the act of scarification is linked to the story of the primitive emotional maturation of a young woman assisted, specifically her interconnection with the body, and how this story is relived in her adolescence. It is intended to reflect on the use of body marks and their identity meanings; about adolescence and its main characteristics; and, some highlights of early emotional development. The present work uses a psychoanalytic method involving a case study aiming to elucidate and explain the act of scarification based on the history of the assisted adolescent and her connection with adolescence. The importance of clinical care for this adolescent was verified and how, based on the establishment of an analytical setting in which she could trust, this adolescent could experience primitive anxieties that were interconnected with her use of scarification